The Italian Cenozoic siliceous sponges: a review, with a revision of the Catullo (1856) collection - Antonio Russo, Ruggero Matteucci (Journal of Mediterranean Earth Sciences, 2014)
Siliceous sponges are known from Eocene, Miocene and Pliocene levels in Italy, but they are poorly investigated. The taxa recognized or erected by authors of the second half of the nineteenth century (T.A. Catullo, A. Manzoni, P. Malfatti) are listed and discussed. The geographical, geological and paleoenvironmental knowledge about the marine levels bearing their rigid skeletal bodies are reviewed. For most of these deposits, the presence of a volcanoclastic input has been evidenced. All the examined original specimens of Catullo’s (1856) siliceous sponge collection, stored at the Geological and Paleontological Museum of University of Padua, are recognized as non referable to siliceous sponges.